Revisiting allostery in CREB-binding protein (CBP) using residue-based interaction energy - ÖZBEK SARICA, PEMRA (SPRINGER, 2020)
CREB-binding protein (CBP) is a multi-subunit scaffold protein complex in transcription regulation process, binding and interacting with ligands such as mixed-lineage leukemia (MLL) and c-Myb allosterically. Here in this study, we have revisited the concept of allostery in CBP via residue-based interaction energy calculation based on molecular dynamics (MD) simulations. To this end, we conducted MD simulations of KIX:MLL:c-Myb ternary complex, its binary components and kinase-inducible domain (KID) interacting domain (KIX) backbone. Interaction energy profiles and cross correlation analysis were performed and the results indicated that KIX:MLL and KIX:c-Myb:MLL complexes demonstrate significant similarities according to both analysis methods. Two regions in the KIX backbone were apparent from the interaction energy and cross correlation maps that hold a key to allostery phenomena observed in CBP. While one of these regions are related to the ligand binding residues, the other comprises of L-12-G(2) loop and alpha(3) helix regions that have been found to have a significant role in allosteric signal propagation. All in all, residue-based interaction energy calculation method is demonstrated to be a valuable calculation technique for the detection of allosteric signal propagation and ligand interaction regions.
Keywords: CREB binding protein (CBP); Allostery; Residue-based interaction energy; Molecular dynamics simulations; Motional correlation analysis; TRANSCRIPTION FACTOR-BINDING; KIX DOMAIN; MOLECULAR-DYNAMICS; TRANSACTIVATION DOMAIN; CELL-GROWTH; COMMUNICATION; COACTIVATOR; P300/CBP; FAMILY; COOPERATIVITY